Pengaruh Kredit Perbankan Terhadap Pertumbuhan Ekonomi dan Hubungannya dengan Kesejahteraan Masyarakat - Paulus Laratmase; Rosdiana; Adi Artino; Sulaiman Efendi Siregar; Try Wahyu Utami (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to analyze the influence of banking credit on economic growth and social welfare. The type of research used in this research is secondary data, namely data in the form of numbers or quantitative time series. The findings in this research are that working capital credit has a positive and significant effect on economic growth, investment credit has a positive and significant effect on economic growth, and credit consumption has a positive and significant effect on economic growth. This means that if working capital credit, investment credit and consumption credit increase, economic growth will also increase. And if economic growth increases, it will encourage social prosperity.